Creating New, Previously Unknown Outcomes: Joy by and by Remade - Moshugi, Kgomotso (Arts Research Africa, The Wits School of Arts, University of the Witwatersrand, 2020)
How can new knowledge be produced through processes of musical arrangement that have not traditionally been canonised? Through analysis of the versions of the hymn Joy By and By, which local arrangers have created since the 1980s, the process of re-imagination and defamiliarisation will be explained.
How can new knowledge be produced through processes of musical arrangement that have not traditionally been canonised? Through analysis of the versions of the hymn Joy By and By, which local arrangers have created since the 1980s, the process of re-imagination and defamiliarisation will be explained.
Keywords: artistic research, arts research, decolonisation, arts pedagogy, decolonisation